A NEW APPROACH TO EXACT PATTERN MATCHING - Nguyen, Truong Huy (Journal of Computer Science and Cybernetics, 2019)
In this paper we introduce a exible approach to design an eective algorithm for exactpattern matching, and compare it with some of the most ecient algorithms, such as AOSO, EBOM,FJS, FSBNDM, HASHq, LBNDM, SA, BMH-SBNDM, SBNDMq, TVSBS. These results are basedon the concept of the degree of fuzziness presented by P. T. Huy et al. in 2002. Theoretical analysesand experimental results indicate that in practice our proposed algorithm is faster than the abovementioned algorithms in most of the cases of patterns and alphabets.